The pathogenesis of zoonotic viral infections: Lessons learned by studying reservoir hosts - Begeman, Lineke; van Riel, Debby; Koopmans, Marion P. G.; Kuiken, Thijs (Frontiers in Microbiology, 2023)
Zoonotic viral infections that cause severe disease or even death in some people may be asymptomatic or mild in reservoir hosts. Comparison of the pathogenesis of these two host categories may potentially explain the difference in disease. However, infections in reservoir hosts are often neglected. Therefore, we compared the pathogenesis of rabies virus, macacine alphaherpesvirus, West Nile virus, Puumala orthohantavirus, monkeypox virus, Lassa mammarenavirus, H5N1 highly pathogenic avian influenza, Marburg virus, Nipah virus, Middle East respiratory syndrome, and simian/human immunodeficiency viruses in both humans and reservoir hosts. We showed that most aspects of the pathogeneses were remarkably similar. The remaining differences lead to the identification of tipping points in the pathogeneses that are important for explaining the disease outcome in severe human cases. Further elucidating these tipping points by studying zoonotic viral infections in their reservoir hosts may teach us how to reduce the severity of zoonotic viral diseases in humans.